Omalizumab improves forced expiratory volume in 1 second in patients with severe asthma - Pałgan, Krzysztof; Żbikowska-Götz, Magdalena; Lis, Kinga; Chrzaniecka, Elżbieta; Bartuzi, Zbigniew (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2018)
Asthma is a multiphenotypic disease, and therapeutic management in patients with severe asthma is particularly difficult, with conventional treatment of severe asthma showing poor efficacy. The inclusion of omalizumab as adjunctive therapy improves asthma control. The studies conducted have shown that omalizumab significantly improves FEV1 after 3 and 12 months of treatment.